(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In recent years, there is increasing interest in using dual-polarization (DP) technique to enable future systems with at least 100 Gb/s rate per channel to operate over existing optical networks. The performance of these advanced systems can be enhanced further by using coherent optical orthogonal multiplexing (CO-OFDM) technique which offers high spectral efficiency and outstanding tolerance of fiber dispersion. This paper addresses the effect of fiber nonlinear optics on the performance of dual-polarization wavelength-division multiplexing (WDM) CO-OFDM systems operating with 100 Gb/s per channel. Different modulation formats, namely BPSK, QPSK and 16-QAM, are used. First, the performance of a single-channel system is investigated in the absence and presence of fiber nonlinearity. The results are compared with a conventional (single-polarization) system to identify the key role played by the DP technique. The investigation is then extended to WDM systems incorporating DP-OFDM technique. The results reveal that the effect of fiber nonlinearity can be reduced by using optimum transmitter laser power Popt. Further, the value of Popt is a function of transmission distance, number of multiplexed channels, and modulation formats. Popt of -11, -12, and -5 dBm is needed for a ten-channel DP system operating with BPSK, QPSK, and 16-QAM formats, respectively. Simulation results presented in this work are obtained using Opti System (version 11.1) which is a commercial software package